Puppies as the primary causal animal for human rabies cases: three-year prospective study of human rabies in the Philippines - Saito, Nobuo; Inton, Karren L.; Mauhay, Jaira D.; Solante, Rontgene M.; Guzman, Ferdinand D.; Yamada, Kentaro; Kamiya, Yasuhiko; Saito-Obata, Mariko; Quiambao, Beatriz P.; Yahiro, Takaaki; Kimitsuki, Kazunori; Nishizono, Akira (Frontiers in Microbiology, 2024)
While rabies remains a global concern, detailed studies on human rabies, particularly regarding causal animals and the reasons for not receiving post-exposure prophylaxis (PEP), are lacking.We conducted a 3-year prospective study (October 2019-September 2022) at the Philippines' largest rabies referral centre. We interviewed patients with suspected rabies and their families.We used LN34 qRT-PCR and rapid fluorescent focus inhibition test on saliva samples. We also compared our findings with two retrospective studies at the same hospital. We enrolled 151 patients, including 131 with potential rabies exposure. Similar to retrospective studies, the participants were predominantly males (75.5%), adults (76.8%), low-income individuals (91.4%), and rural dwellers (62.3%). The causal animals were mainly dogs (97.0%), with similar incubation periods, clinical symptoms, and a high proportion not receiving vaccines or immunoglobulins (93.2%). Most causal animals were owned by either the patients' households or their neighbours (60.2%), with a significant proportion being puppies (58.8%). Most patients had knowledge of rabies; however, reasons for not seeking PEP included misconceptions about minor bites not causing rabies (51.3%), beliefs in traditional healers (33.9%), and economic constraints (22.6%). Despite completing the WHO regimen, two PEP failures were observed.LN34 qRT-PCR detected 98 positive cases (sensitivity, 64.9%; 95% CI 56.7-72.5). These strains belong to the Southeast Asia 4 subclade. In conclusion, this study highlights the role of